The use of anchored words and the discontinued words in the case of their enunciation in the narration of Robb-Grillet: (The jealousy) selected as a sample - Hasan, Lubna Abdullah Mohammed (Al-Adab Journal, 2019)
Social communication, whether oral or written, contains the word and the enunciation at the same time. These two concepts constitute the interaction within the community where the latter is a unilateral act through which the speaker produces the word and directs it to the recipient, either alone or combination, in a specific condition. These two concepts play an important role in narrating Robbe-Grillet’s novel (The jealousy). His narrative is a modern novel manner that presents us with scenes showing the life of a jealous husband over his wife by using metaphor. We feel his jealousy indirectly through the use of repetition in some scenes which revolve in an endless need with the use of the present time in most details of the novel. In this research we try to address the questions related to the importance of using anchored word and the use of discontinued word about the situation of enunciation which was used by the narrator Robbe-Grillet in his novel (The jealousy). We found that the narrator uses the anchored word to express the condition of speech exchange, but he, in the other hand, used the discontinued word to clarify the narrative leaps